The critical role of BAP1 mutation in the prognosis and treatment selection of kidney renal clear cell carcinoma - Tan, Guobin (Transl Androl Urol, 2020)
BACKGROUND: The BAP1 mutation is commonly found kidney renal clear cell carcinoma (KIRC) and a potential biomarker of individualized therapy. We evaluated the clinical significance of BAP1 mutation in the prognosis and treatment therapies for KIRC. Potential key pathways and related genes associated with these mechanisms were also identified in this investigation. METHODS: We identified the relevant data of patients BAP1 mutated on the cBioPortal and the compounds with significant selectivity to BAP1 mutations on the Genomics of Drug Sensitivity in Cancer (GDSC). And then, we identified the differences in mRNA expression levels of biological function annotation and pathways between mutated and wild type BAP1 patients by GSEA analysis. Furthermore, we screened the differentially expressed genes (DEGs) between BAP1 mutated and wild typed in KIRC patients and performed the GO and KEGG analysis. Finally, we conducted a protein-protein interaction (PPI) network to investigate the interaction between proteins encoded by candidate DEGs. RESULTS: Review of the TCGA data revealed 41 patients (10%) with KIRC displayed the BAP1 mutation. Further analysis led to the identification of 730 DEGs, while 617 genes were shown to be down-regulated, with 113 genes displaying upregulation. GO and KEGG pathway analysis indicated DEGs as enriched in metabolism, drug metabolism-cytochrome P450, and Drug-metabolizing enzymes. Subsequently, the top 10 hub genes, ranked by the degree in the PPI network were identified. Furthermore, our findings verify that the BAP1 mutation was associated with the deterioration of prognosis in patients with KIRC. Additionally, analysis of the GDSC database revealed that KIRC patients with BPP1 mutation are more prone to responding to Linsitinib. CONCLUSIONS: Our investigation identified the main pathways and relevant genes related to the BAP1 mutation in KIRC, which can contribute to the development of targeted treatment strategies for enhanced prognostic predictions of KIRC.